Analisis Impulsive Buying E-Commerce: Studi pada Pengguna Shopee - Hardyansah; Christian Wiradendi Wolor; Rahmi (Journal of Business Application, 2024)
The research aims to find out what factors influence the impulsive buying behavior of e-commerce Shopee users where a survey was conducted on 120 people in Jabodetabek using a quantitative method of distributing questionnaires online. This research uses data collection techniques, namely questionnaires and literature study. This research uses analytical techniques with descriptive analysis and confirmatory factor analysis (CFA). The results of this research found that the highest factor regarding impulsive buying is the brand. It is hoped that this study can be used as consideration for consumers so that they do not become impulsive buyers in e-commerce and as material for decision making regarding triggers that do not become a necessity when there is an e-commerce program.